Collaboration Innovation for Optimizing Village Potentials through the Bermasa Program in Bengkalis Regency - Adianto; Mayarni; Dedi Kusuma Habibie; Risky Arya Putri; Ahmad Hadi (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2025)
This research analyzes the Collaborative Innovation approach for optimizing village potentials through the BERMASA program in Bengkalis Regency by using the bibliometric analysis research method to find research gaps and novelty as well as empirical and secondary analysis, namely using a qualitative approach. Problem-solving plans and research objectives from this research to promote collaborative innovation effectively within the context of the BERMASA program in Bengkalis Regency, it is essential to identify and address the barriers that hinder collaborative efforts. This research found that the village government plays the most significant role in the collaborative innovation process in government as the front guard and the actor closest to the community. This collaborative innovation approach is considered capable of meeting sustainability standards and improving community welfare in an integrated manner following the development vision of the Bengkalis Regency government through the BERMASA program. Therefore, this research recommends the Pentahelix approach to maximize innovation-based collaboration, which can increase the role of actors in a more structured manner according to their tasks and functions, both explicitly and in general. It is also hoped that equal access to internet networks and transportation in remote villages in Bengkalis Regency will be immediately addressed to optimize innovations initiated by the village government and the community.